Species-specific real-time PCR cell number quantification of the bloom forming cyanobacterium Planktothrix agardhii - Churro, Catarina (2012)
A species-specific method to detect and quantify Planktothrix agardhii was developed by combining the SYBR Green I real-time polymerase chain reaction technique with a simplified DNA extraction procedure for standard curve preparation. Newly designed PCR primers were used to amplify a specific fragment within the rpoC1 gene. Since this gene exists in single copy in the genome, it allows the direct achievement of cell concentrations. The cell concentration determined by real-time PCR showed a linear correlation with the cell concentration determined from direct microscopic counts. The detection limit for cell quantification of the method was 8 cells μL−1, corresponding to 32 cells per reaction. Furthermore, the real-time qPCR method described in this study allowed a successful quantification of P. agardhii from environmental water samples, showing that this protocol is an accurate and economic tool for a rapid absolute quantification of the potentially toxic cyanobacterium P. agardhii.